Multi-objective distributed generation penetration planning with load model using particle swarm optimization - Ganguly, Sanjib (Decision Making: Applications in Management and Engineering, 2020)
The paper presents an approach for simultaneous optimization of Distributed Generation (DG) penetration level and network performance index to obtain the optimal numbers, sites, and sizes of DG units. Two objective functions are formulated. These are: (II) DG penetration level, (II) network performance index. The minimization of the first objective reduces the capital investment cost of a distribution network owner (DNO) to integrate DG. The minimization of the second objective helps in reduction of network losses and improvement in node voltage profile and line loading. The solution approach provides a set of non-dominated solutions with different values of DG penetration level and network performance index. Thus, it offers more flexibility to a DNO to choose a final solution from the set of solutions according to its strategic decisions, regulatory directives, and budget restrictions. The solution approach used is multi-objective particle swarm optimization. The approach is validated on a 38-node distribution system. The results are compared with some existing approaches